Gross-Anatomical and osteometric investigations on sternum in Quails - Ozkan, Zait Ender (My University, 2004)
The main gross anatomical features of the sternum in quails (Coturnix coturnix) were the developed carina sterni and triangular rostrum sterni. There was no foramen rostri.
Keywords: Animalia; Coturnix; Coturnix coturnix; Phasianidae; anatomy; animal experiment; animal tissue; article; bone development; controlled study; female; male; nonhuman; osteometry; quail; sternum